Intracranial Atherosclerotic Disease-Related Acute Middle Cerebral Artery Occlusion Can Be Predicted by Diffusion-Weighted Imaging - Zhang, Huijun; Sun, Xuan; Huang, Qiong; Wang, Xiangming; Yue, Yunhua; Ju, Mingfeng; Wang, Xiaoping; Ding, Ji; Miao, Zhongrong (Frontiers in Neuroscience, 2019)
Background: Differentiation of large vessel occlusion caused by intracranial atherosclerotic stenosis (ICAS) or intracranial embolism significantly impacts the course of treatment (i.e., intravenous thrombolysis versus mechanical thrombectomy) for acute cerebral infarction. Currently, there is no objective evidence to indicate ICAS-related middle cerebral artery M1 segment occlusion before treatment. In cases of ICAS, it is often observed that the infarct core caused by ICAS-related M1 segment middle cerebral artery occlusion (MCAO) is located in deeper parts of the brain (basal ganglia or semiovoid region). Objective: To evaluate whether the location of the infarct core, identified using diffusion-weighted imaging (DWI), can be used to differentiate ICAS from intracranial embolism. Methods: Thirty-one consecutive patients diagnosed with acute cerebral infarction caused by middle cerebral artery M1 segment occlusion were retrospectively included based on angiographic findings to distinguish ICAS from embolic occlusion. Patients were divided into two groups based on the location of the infarct core on DWI: in the deep part of the brain (basal ganglia or semiovoid region) or more superficially (i.e., cortex). Results: In 16 patients, the infarct core was mainly in the deep part of the brain on DWI (14 of 16 patients in the ICAS group and only 2 in the non-ICAS group [93.3% versus 6.7%, respectively; P<0.001]). The diagnostic sensitivity of DWI for ICAS was 93.3%, with a specificity of 87.5%, a PPV of 87.5%, and an NPV of 93.3%, the accuracy was 88.5%. Conclusion: Intracranial atherosclerotic disease-related acute MCAO can be predicted using DWI.